ANALISIS DAN EVALUASI SALURAN DRAINASE PADA JALAN JAMBORE KELURAHAN CIBUBUR KECAMATAN CIRACAS JAKARTA TIMUR - Ismono Kusmaryono; Reza Budiman (Jurnal Sipil Krisna, 2023)
Jalan Jamboree, Cibubur Village, Ciracas District, often experiences puddles during the rainy season. This studyaims to analyze and evaluate whether the dimensions of the drainage channel meet the requirements for runoffdue to rainwater. The case study analysis method uses rainfall data from BMKG which is then carried outhydrological analysis using the Pearson Log III method, rain intensity analysis using the Mononobe method andflow discharge analysis using the rational method taking into account the existing water catchment area so thatthe actual ditch dimensions can be determined. The evaluation results show that the dimensions of the existingditch do not meet the drainage requirements of rainwater runoff, where the existing ditch water discharge(Qs=0.748 m3/second) < design water discharge (Qt=1.481 m3/second). Second). Re-calculation of channeldimensions produces the following dimensions: width (b) of 0.9 m, height (h) of 2 m or using precast with width(b) of 1.2 m and channel height (h) of 1.2 m.